Occurrence and 15N-quantification of simultaneous nitrification and denitrification in N-fertilised soils incubated under oxygen-limiting conditions. (April 2020) - Castellano-Hinojosa, Antonio; Charteris, Alice F.; Müller, Christoph; Jansen-Willems, Anne; González-López, Jesús; Bedmar, Eulogio J.; Carrillo, Presentación; Cárdenas, Laura M.
Abstract: Nitrification and denitrification are known to co-occur in soils, but the effect of fertilisation history on N2 O fluxes and the relative source partitioning of the N2 O has not been thoroughly investigated. In this study, we therefore combined a high-tech 15 N stable isotope tracing technique with quantitative PCR (qPCR) to explore the relative contributions of nitrification and denitrification to N2 O production by a sandy-loam Eutric Cambisol soil treated repeatedly with ammonium sulfate [(NH4 )2 SO4 ] or potassium nitrate (KNO3 ) for 3 years prior. Both soils (historically (NH4 )2 SO4 and historically KNO3 treated) were amended separately with ( 15 NH4 )2 SO4 and K 15 NO3 and incubated at 80% water filled pore space for 30 days. Soil N2 O emissions, NH4 + and NO3 − concentrations and their corresponding 15 N-enrichments were determined. The effect of N addition on N transformation rates was also calculated. The total abundance of nitrifiers was estimated by qPCR of the amoA gene from bacteria and archaea, and that of denitrifiers by using the nirK, nirS, norB and nosZ I genes as molecular targets. In the historically (NH4 )2 SO4 -treated soil, 49.0–58.0% of the N2 O emitted originated from nitrification and 42.0–51.0% from denitrification during incubation. The production of N2 O was accompanied by a decrease in soil NH4 + concentrations and a parallel increase in the concentration of soil NO3 − . In addition, the abundance of the bacterial and archaeal amoA gene increased during the incubation. Conversely, in the soil historically treated with KNO3, the 15 N isotopic analyses showed that denitrification contributed 84.0–99.0% of the total N2 O produced. Decreases in soil NO3 − concentrations paralleled the increase in 15 N enrichment of N2 O and the abundance of the nirK, nirS, norB and nosZ I genes. The results also showed that values of 15 N2 enrichment were significantly higher in the KNO3 -treated soil, which is in line with the higher abundance of the nosZ I gene. Calculation of the N transformation rates indicated that autotrophic nitrification and denitrification were responsible for N2 O production in the historically (NH4 )2 SO4 -treated soil and that denitrification was the most important N2 O source in the soil treated with KNO3 . We conclude that N-fertilisation history, and not simply soil oxygen availability, affect the relative contributions of nitrification and denitrification to soil N2 O emissions. Indeed, here we have shown that nitrification can be an important N2 O source process even in soils maintained at high moisture contents. Highlights: There exist simultaneous nitrification and denitrification in suboxic N-fertilised soils. Rates of 15 N2 O enrichment from each process were similar in NH4 + treated soils. Denitrification exceeded nitrification when NO3 − was the applied fertiliser. In that case, the highest 15 N2 O enrichment was due to 15 NO3 −, not to 15 NH4 + . The targeted nitrification and denitrification genes increased during soil incubation.